A Service Evaluation of the Experiences of Patients With Functional Neurological Disorders Within the NHS - O'Keeffe, Shauna; Chowdhury, Ibrahim; Sinanaj, Anila; Ewang, Iberedem; Blain, Camilla; Teodoro, Tiago; Edwards, Mark; Yogarajah, Mahinda (Frontiers in Neurology, 2021)
Previous research into Functional Neurological Disorder (FND) has shown that there are significant barriers in providing patient-centred care. However, there has been no specific research into whether patient experiences of care for FND meet the current standards of care. This study aimed to investigate the types of problems experienced by FND patients, and whether these differed to patients with multiple sclerosis (MS). FND (n = 40) and MS patients (n = 37) were recruited from NHS tertiary neurology clinics and completed questionnaires on their experiences of health care services. Significant differences in experiences of care between the two patient groups were found, with FND patients reporting significantly more problems in their diagnosis and treatment (p = 0.003), patient-centred care (p < 0.001), relationships with healthcare professionals (p < 0.001), and in accessing community care (p = 0.001). Limitations include a small sample size, specificity to a single centre, and cross-sectional design. The results suggest that current care for FND patients is not meeting expected standards for long-term neurological conditions, highlighting the need for structured care pathways and patient-centred care.